PENGARUH KOMPREHENSIF ATAS STRATEGI MODAL KERJA MELALUI RASIO PERDAGANGAN (Merchandising Ratio) - Wenty ,; Murtanto , (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2001)
The implementation of working capital strategy of successful companies could be observed from its cash conversion cycle. Effective working capital strategy will lead to an increasing to an increase of a firm's value. This thesis has two objectives : Firstly, it analyse the interrelationships between the merchandising ratio with the return on assets ratio and the long-term debt to total assets ratio. These two ratios have the ability to check the effectiveness of a firm's working capital management. Secondly, it analyse the effective of the firm's management of cash, receivable, inventory and payables.The writer is using the descriptive analysis method which describe the retail firm's working capital strategy from the financial statement information, and the correlation analysis method that detects the correlation between the merchandising ratio and the traditional ratio.The analysis shows that PT Hero Supermarket, PT Matahari Putra Prima and PT Ma Retailindo have good and effective working capital strategy. The merchandising ratio has positive correlation with the return on assets ratio and negative correlation with the debt to total assets ratio.The purpose of this research is to prove the effectiveness in using the cash conversion cycle strategy. PT Hero Supermarket, PT Matahari Putra Prima and PT Alfa Retailindo should emphasize on their inventory management so that the percentage of sales growth is accompled by an equivalent increase in its inventory. Apart from that, these compa Iles should focus on their payables management by maximize the debt benefit.Crucial terms: working capital strategy, merchandising ratio and cash conversion cycle.